Influence of NaCl-Induced Salinity and Cd Toxicity on Respiration Activity and Cd Availability to Barley Plants in Farmyard Manure-Amended Soil - Adel R. A. Usman (Applied and Environmental Soil Science)
The objective of this study was to evaluate the Cd availability and toxicity as affected by NaCl-induced salinity and farmyard manure addition. The Cd availability and toxicity were investigated in greenhouse pot and incubation experiments were conducted on a calcareous loamy sand soil contaminated with Cd (0.5, 1.5, 3, 6, 12, and 24 mg kg−1 of soil) and amended with two rates of 0.0 and 30 g farmyard manure (FYM) kg−1. Barley seeds (Hordeum vulgare L.) were sown in pots and irrigated with water containing different levels of salinity (0, 30, 60, and 120 mM NaCl). The results revealed that the DTPA-extractable Cd and its content in barley plant shoots tended to increase in line as Cd was applied and salt levels increased. Elevated decreases in the soil basal respiration with increased Cd applied and NaCl-induced salinity were found. However, applying FYM significantly reduced Cd availability and increased plant growth and soil respiration activity. The results clearly showed that adding farmyard manure as soil organic amendment decreased the availability of Cd to barley plants and mitigated the toxicity of both Cd and salinity to soil microbial activity.